VARIASI KETEBALAN IRISAN, JENIS MINYAK DAN SUHU PENGGORENGAN TERHADAP RASA DAN KERENYAHAN KERIPIK APEL YANG DIOLAH DENGAN VACCUM FRYING - Wulandari, Septiani Dwi; Riyanto; Mistianah (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2017)
Poncokusumo is a village in East Java which most of the people work as a farmer. One of it’s comodities was apple fruit, and the products that have being popular now was apple’s chips. Nowdays people usually use vaccum friying technology to produce apple’s chips. There were some factors that can effect the apple’s chips quality such as slices thickness, oil type and vacuum frying temperature. This is a descriptive quantitative research that want to describe how the variations of slice thickness (K), type of oil (M), and vacuum frying temperature (S) effect the apple’s chips flavor and crispness. The response was organoleptic preference level of the flavor and crispness, chemical analyzes performed on water content, fat content, and carbohydrate content. The results showed there are difference flavor and crispness with variation of slice thickness, type of oil, and vacuum frying temperature. The organoleptic test also showed that most preferred apple’s chips have low water levels, low fat content and high carbohydrate content. The most preferred apple’s chips was chips that have 3 mm of slice thickness, use coconut oil and frying at 850C.